Prevalence of depression, anxiety in China during the COVID-19 pandemic: an updated systematic review and meta-analysis - Bin, Xiang; Qu, Ke-Yi; Wang, Yu-Hao; Chen, Li; Xiong, Yan-Jie; Wen, Jin Fu; Wei, Hua-Bo; Bing, Tan; Dan, Chun-Yan; Zhu, Jia-Quan (Frontiers in Public Health, 2024)
Background: Mental health risks associated with the aftermath of the COVID-19 pandemic are often overlooked by the public. The aim of this study was to investigate the effects of the COVID-19 pandemic on depression and anxiety disorders in China.Studies were analyzed and extracted in accordance with PRISMA2020 flowchart.The studies were screened and extracted using electronic databases including PubMed, Web of Science, Embase, Cochrane Library, and Clinical Trials.gov according to predefined eligibility criteria. The Cochrane Review Manager software 5.3.1 was used for data analysis as well as the risk of bias assessment.Results: As of 2023, a total of 9,212,751 Chinese have been diagnosed with COVID-19 infection. A total of 913,036 participants in 44 studies were selected following the eligibility criteria, the statistical information of which was collected for meta-analysis. The pooled prevalence of depression and anxiety were 0.31 (95% CI: 0.28, 0.35); I 2 = 100.0%, P < 0.001 and 0.29 (95% CI: 0.23, 0.36); I 2 = 100.0%, P < 0.001, respectively. After performing subgroup analysis, the prevalence of depression among women, healthcare workers, students, and adolescents was 0.31 (95% CI: 0.22, 0.41), 0.33 (95% CI: 0.26, 0.44), 0.32 (95% CI: 0.26, 0.39) and 0.37 (95% CI: 0.31, 0.44), respectively.The prevalence of depression and anxiety among the Chinese was overall high.Monitoring and surveillance of the population mental health status during crises such as sudden global pandemics is imperative.